2020
DOI: 10.1177/0954408920968351
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on resistance spot welding of dissimilar weld joints

Abstract: In the present study, galvanized High Strength Interstitial Free (HIF) steel sheets, and Dual Phase (DP780) steel sheets were used for the investigations. Resistance spot weld joints were fabricated between dissimilar steel sheets. The variation in dynamic resistance (DR) with the change in welding process parameters such as weld current, weld time and electrode force were used for establishing the range of adequate weld nugget formation parameters. Effect of these parameters over tensile strength, nugget diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…They observed that the size of the fusion zone and the failure mode were the most critical factors in the quality of welding. Verma et al 13 studied the effect of the welding current (WC) and the welding time (WT) parameters over the tensile strength, the nugget diameter, and the failure mode using one factor at a time approach. Daneshpour et al 14 made RSW and LSW joints of DP780-DC04 steels and investigated these joints’ mechanical properties, failure modes, and fatigue life analyses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the size of the fusion zone and the failure mode were the most critical factors in the quality of welding. Verma et al 13 studied the effect of the welding current (WC) and the welding time (WT) parameters over the tensile strength, the nugget diameter, and the failure mode using one factor at a time approach. Daneshpour et al 14 made RSW and LSW joints of DP780-DC04 steels and investigated these joints’ mechanical properties, failure modes, and fatigue life analyses.…”
Section: Introductionmentioning
confidence: 99%
“…There are important studies conducted on microstructuretensile shear properties of RSW welded various steel sheets. 1,4,8,[10][11][12][13] In addition, some important literature based on the work conducted on RSW of the DDS, 6,[14][15][16][17][18][19][20] is discussed here as under. Boriwal et al 1 investigated the effect of process parameters on the strength of the welded joint of 304L and low-carbon steel sheets.…”
Section: Introductionmentioning
confidence: 99%
“…24 A significant amount of research has been carried out on this joining process. [25][26][27][28][29][30][31][32][33] For example, Verma et al, 25 Krishnan et al, 26 and Boriwal et al 29 investigated welding parameters effects on tensile strength, nugget geometry, failure mode, and hardness of RSW welded High Strength Interstitial Free-Dual Phase (DP780), austenitic stainless steel AISI 316 L-duplex stainless steel 2205, austenitic stainless steel 304L-low carbon steel sheets, respectively. In addition, Boriwal et al 27 used surface response methodology for process analysis and regression modeling of RSW welded austenitic stainless steel 304L-low carbon steel sheets.…”
Section: Introductionmentioning
confidence: 99%
“…The development of advanced high strength steels (AHSS) was the response of the steel industry to the demands of the automotive sector in terms of reducing the weight of vehicle structures without compromising their mechanical properties, in addition to other advantages such as cost reduction, safety performance and good weldability [1,2]. Dual-phase (DP) steel is one of the most widely used AHSS in the automotive industry, particularly in the manufacturing of car bodies [3,4].…”
Section: Introductionmentioning
confidence: 99%